2018
DOI: 10.4149/km_2017_6_421
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and precipitation strengthening of fully lamellar Ti-45Al-5Nb-0.2B-0.75C alloy

Abstract: The alloy with a composition Ti-45Al-5Nb-0.2B-0.75C (at.%) was prepared by induction melting and centrifugal casting. The fully lamellar microstructure of the alloy without carbides was produced by heat treatment consisting of hot isostatic pressing (HIP) and solution annealing followed by cooling to room temperature. The stability of the fully lamellar γ(TiAl) + α2(Ti3Al) microstructure was studied at temperatures of 750, 850 and 950• C up to an ageing time of 3400 h. The microstructure analysis shows that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The unique combination of both metallic and ceramic properties of Ti 2 AlC, such as high fracture resistance, excellent damage tolerance, good thermal and electrical conductivity, easy machinability, good thermal shock and oxidation resistance, high elastic modulus and thermochemical stability benefit fabrication of insitu composites [12][13][14][15][16]. Besides the coarse primary Ti 2 AlC particles, the additional strengthening of the in-situ composites can be achieved by fine secondary needle-like perovskite P-Ti 3 AlC and plate-like hexagonal H-Ti 2 AlC precipitates forming in the TiAl matrix and along grain boundaries as has been observed in several carbon-containing TiAl-based alloys [17][18][19][20].…”
Section: Introductionmentioning
confidence: 88%
“…The unique combination of both metallic and ceramic properties of Ti 2 AlC, such as high fracture resistance, excellent damage tolerance, good thermal and electrical conductivity, easy machinability, good thermal shock and oxidation resistance, high elastic modulus and thermochemical stability benefit fabrication of insitu composites [12][13][14][15][16]. Besides the coarse primary Ti 2 AlC particles, the additional strengthening of the in-situ composites can be achieved by fine secondary needle-like perovskite P-Ti 3 AlC and plate-like hexagonal H-Ti 2 AlC precipitates forming in the TiAl matrix and along grain boundaries as has been observed in several carbon-containing TiAl-based alloys [17][18][19][20].…”
Section: Introductionmentioning
confidence: 88%
“…The C20 and C36 alloys used for the evaluation of microstructural stability and mechanical properties were subjected to the heat treatment after HIP-ing. The heat treatment consisted of solution annealing in the single β phase field at a temperature of 1460 • C followed by cooling at a constant cooling rate of 15 • C/min and stabilization annealing at 850 • C for 25 h. Several authors [12,15,16,19,27,33] have shown that the stabilisation annealing in a temperature range from 800 to 900 • C leads to the formation of fine secondary P-Ti 3 AlC and H-Ti 2 AlC precipitates along α 2 /γ lamellar interfaces, which significantly improve the high temperature creep resistance of carbon-containing TiAl-based alloys. Figure 4 shows the typical microstructure of the heat-treated (HT) alloys.…”
Section: Effect Of Heat Treatment On Microstructurementioning
confidence: 99%
“…It is well known that substitutional elements like Nb, Mo, Ta, and W as well as the interstitial elements such as C improve high temperature creep resistance of TiAl-based alloys [9][10][11][12][13]. The addition of carbon up to about 0.8 at.% contributes to precipitation strengthening through the formation of two types of fine carbides: cubic perovskite-type Ti 3 AlC (P-type) with needle-like morphology and hexagonal Ti 2 AlC (H-type) with plate-like morphology [12,[14][15][16]. Higher content of carbon (above 1 at.%) leads to the formation of coarse primary H-type carbide particles during solidification [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the strength and resistance to creep is improved through the formation of Ti 3 AlC perovskite precipitates when C is added. Numerous work has been conducted to date [130][131][132][133][134] on the effect B and C have on the microstructure and mechanical properties of TiAl, attesting to the above alloy addition benefits.…”
Section: St and 2nd Generation Of Tial Alloysmentioning
confidence: 99%